PENGARUH SUMBER DAYA MANUSIA TERHADAP PROFESIONALISME PRAJURIT PANGKALAN TNI AL DI PANTAI BARAT - Bambang Supriyono; Prio Budi Leksono; Devi Erlita (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
Naval base as one of the integral components of the SSAT is the spearhead of power in carrying out support for the tasks of the operating units both in peacetime and during war. In carrying out its duties the Navy has an Integrated Fleet Weapon System (SSAT) which is the integration of strength of the capabilities of the KRI, Aircraft, Marines and Naval base components. To find out the professional level of the soldier, it is necessary to hold a Test of Combat Naval Base Task Force in order to realize, maintain and improve the skills of both individuals and groups, which in turn will increase the establishment of Operational Command and Control, Operational Procedures and the establishment of mastery of appropriate techniques and tactics. With the implementation of the test, it is expected to know about Naval Base Combat Readiness, a condition where the base can carry out its main tasks. Combat Duty Rehearsal is an exercise carried out by KRI or base to maintain the ability and professionalism of soldiers both programmed and programmed. This study aims to determine whether the relationship of human resource readiness influences the professional abilities of the Naval Base on west coast.